Physicochemical efects of lactose microcarrier on inhalation performance of rifampicin in polymeric nanoparticles / Ainne Nabila Noraizaan - Noraizaan, Ainne Nabila (2016)
This study investigated the effects of size, size distribution, specific surface area, surface roughness, crystallinity, and fine content (< 5 pim fraction) of lactose microcarrier on the pulmonary inhalation profiles of rifampicin encapsulated in polyvinylpyrrolidone nanoparticles (194.77 ± 9.52 ran). The spherical lactose was modified through solvation and reprecipitation processes using aqueous ethanolic solution with different ethanol contents. The reprecipitated lactose had smaller particle size, wider size distribution, larger specific surface area, more elongated shape, smoother surface texture and lower crystallinity than the unprocessed lactose. They contained fine particles of sizes smaller than 5 /an of which none was found in the unprocessed lactose. Cascade impactor and scanning electron microscopy analysis of lactose-nanoparticle blends indicated that unprocessed lactose carried nanoparticles through surface adsorption and pore immersion methods. The small, less crystalline and elongated processed lactose carried nanoparticles through surface adsorption and encapsulation via inter-lactose aggregation. The aggregative tendency of these lactoses increased with reduced size and crystallinity and a increased surface roughness that provided more active sites for particulate interaction. This improved the fine particle dose, fine particle fraction, percent dispersed, percent inhaled of nanoparticles due to their ability to remain attaching to lactose during aerosolization, and detach for deep lung deposition in late time domain unlike those immersed in pores of unprocessed lactose. Overall, a lactose fine content amounting to less than 9 % or more than 12 % was detrimental to aerosolization. Excessive fine reduced nanoparticle attachment. Suboptimal fine content discouraged nanoparticle detachment and deposition.